THE EFFECT OF HUMAN RESOURCE QUALITY AND GOVERNMENT ACCOUNTING STANDARDS ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORTS IN EAST LOMBOK REGENCY - Salsabila Salsabila (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effect of human resource quality and the implementation of Government Accounting Standards (SAP) on the quality of financial reports of the East Lombok Regency Local Government, both partially and simultaneously. The study employed a quantitative approach using primary data collected through a questionnaire distributed to civil servants (ASN) working in the finance departments of Regional Government Agencies (OPD) in East Lombok Regency. The study population consisted of 86 individuals, and a saturation sampling technique was used. A total of 49 questionnaires were processed and analyzed using SPSS software through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and the coefficient of determination. The results indicate that the quality of human resources and the implementation of Government Accounting Standards influence the quality of local government financial reports. Simultaneously, these two variables contribute to improving the quality of financial reports, making them relevant, reliable, comparable, and easy to understand. Therefore, enhancing the competence of civil servants and consistently implementing Government Accounting Standards are crucial factors in achieving accountable and transparent local financial management.